Rapid, High‐Resolution 3D Interference Printing of Multilevel Ultralong Nanochannel Arrays for High‐Throughput Nanofluidic Transport. (2nd November 2015) - Park, Junyong; Kim, Kyung‐Il; Kim, Kisun; Kim, Dae‐Chul; Cho, Donghwi; Lee, Jung Heon; Jeon, Seokwoo
Abstract : 3D interference printing enables the single‐step production of multilayered ultralong nanochannel arrays with nanoscale regularity. The superior depth‐of‐focus of this technique realizes a state‐of‐the‐art nanostructure which has intensively stacked 32 layers of inch‐long, horizonontal nanochannels with sub‐100 nm holes in a monolithic matrix (≈15 μm). This exceptional structure can be integrated into microfluidic devices, facilitating high‐flux rheological platforms using nanocapillarity.